Increasing milk production ability of lactating cows through improvement of feeding managemen - Siregar, Sori B (Indonesian Animal Sciences Society, 2001)
Increasing milk production ability of lactating cows through improvement of feeds and feeding frequency was conducted at Tanjungsari Village Cooperative. Fifteen lactating cows of 3-4 months of lactation period were used. The cows were divided into five groups based on their average daily milk production and lactation period. The treatment consisted of RO (control=commonly practiced by farmers), R1 (2.5 kg. concentrate, given three times per head per day). R2 (2 kg. Concentrate plus 13.5 kg roughage given three times per head per day). The experimental design was completely randomized block design. The quality of concentrate given to the lactating cows was a better than that given by the local farmers. Improving feed supplementation and feeding frequency significantly (P<0.01) increased the consumption of dry matter, crude protein and Â energy of the feeds, and thus increased daily milk production, solid non fat (SNF) and total solid (TS) of the milk (P<0.05). Specific gravity of the milk was not affected by the treatments (P>0.05). Substitution of 0.5 kg concentrate with 13.5 kg roughage resulted in non significant difference on the daily milk production as well as the quality of the milk, thus it gave no economic impact. The increase of daily milk production was followed by the increase of the incomes of the farmers by Rp 905 to Rp 1,425 per head per day. The result of the experiment leads to the assumption that the present feeding practices of the lactating cows should be improved accordingly. Â Key words: Lactating cows, feeding, management